2018
DOI: 10.1002/ccr3.1329
|View full text |Cite
|
Sign up to set email alerts
|

The histopathology and phenotypic variability in H syndrome

Abstract: Key Clinical MessageSkin biopsy may be helpful in the diagnosis of H syndrome. A triad of dermal fibrosis, lymphocytic aggregates, and numerous CD68+, CD163+, S100‐positive, and CD1a‐negative dermal histiocytes is characteristic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Histopathologic evaluation of indurated and hyperpigmented skin in H syndrome reveals melanin deposition, significant thickening of collagen fibers in upper and mid dermis, perivascular histiocytic and histiocyte‐like cell proliferations, and presence of many fibroblasts and dense lymphocyte aggregates usually highly positive for Ki‐67 in immunohistochemical staining. It is plausible that these inflammatory cells are suppressed by immunomodulatory drugs providing an explanation of the efficacy of mycophenolate mofetil on H syndrome resulting in lightening of skin pigmentation and lessening of skin induration, similar to other clinical conditions with similar histopathological characteristics 10,11 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Histopathologic evaluation of indurated and hyperpigmented skin in H syndrome reveals melanin deposition, significant thickening of collagen fibers in upper and mid dermis, perivascular histiocytic and histiocyte‐like cell proliferations, and presence of many fibroblasts and dense lymphocyte aggregates usually highly positive for Ki‐67 in immunohistochemical staining. It is plausible that these inflammatory cells are suppressed by immunomodulatory drugs providing an explanation of the efficacy of mycophenolate mofetil on H syndrome resulting in lightening of skin pigmentation and lessening of skin induration, similar to other clinical conditions with similar histopathological characteristics 10,11 …”
Section: Discussionmentioning
confidence: 97%
“…Bioinformatics analysis suggested that this mutation is likely pathogenic with a CADD phred score of 29, and the allelic fre- characteristics. 10,11 Previously in Iran, three other cases of H syndrome have been documented. Two of the cases were initially misdiagnosed, one of them as morphea and the second one as juvenile idiopathic arthritis, but neither one received any therapies for their cutaneous presentations.…”
Section: Case Reportmentioning
confidence: 99%
“…Hence, patients with the same SLC29A3 mutation present with variable features based on the different trauma/triggers imposed on various tissues (a type of Koebner response). For instance, attacks of otitis preceded development of hearing loss 5,10 . Moreover, Koebner phenomenon was reported in another form of histiocytosis (xanthoma disseminatum) 11 .…”
Section: Discussionmentioning
confidence: 98%